Women's activism behind the screens : trade unions and gender inequality in the British film and television industries - Galt, Frances (Bristol University Press, 2020)
Frances C. Galt explores the role of trade unions and women's activism in the British film and television industries in this important contribution to debates around gender inequality.
Description based upon print version of record.
Keywords: Women in the motion picture industry -- Great Britain.; Women labor union members -- Great Britain.; Motion picture industry -- Employees -- Labor unions -- Great Britain.; Television broadcasting -- Employees -- Labor unions -- Great Britain.; Sex discrimination in employment -- Great Britain.; Femmes dans l'industrie cinématographique -- Grande-Bretagne.; Cinéma -- Industrie -- Personnel -- Syndicats -- Grande-Bretagne.; Télévision -- Personnel -- Syndicats -- Grande-Bretagne.; Discrimination sexuelle dans l'emploi -- Grande-Bretagne.; POLITICAL SCIENCE / Labor & Industrial Relations.; Motion picture industry -- Employees -- Labor unions; Sex discrimination in employment; Television broadcasting -- Employees -- Labor unions; Women in the motion picture industry; Women labor union members; Great Britain; Electronic books.